CD18 Mediates Neutrophil Imperviousness to the Aggregatibacter actinomycetemcomitans JP2 Clone in Molar-Incisor Pattern Periodontitis - Hashai, Koren; Chapple, Ian L.; Shapira, Lior; Assadi, Walaa; Dadon, Stav; Polak, David (Frontiers in Immunology, 2022)
Introduction: Molar-incisor pattern periodontitis (MIPP) in the absence of significant local risk factors, is a rare, early onset periodontal disease phenotype, with 0.5% to 2.5% global prevalence. The condition is characterized by impaired neutrophil function and persistent Aggregatibacter actinomycetemcomitans (JP2 clone) infection. The aim of this study was to characterize neutrophil functional responses to JP2 and to investigate the neutrophil receptors involved. Materials and methods: Neutrophils were obtained from whole blood samples of periodontally healthy and MIPP subjects and incubated with the JP2 clone or a non-JP2 clone of A. actinomycetemcomitans. Bacterial survival was tested by blood agar culture; neutrophil death was tested with propidium iodide and flow cytometry; Reactive oxygen production (ROS) was measured with 2′,7′-dichlorofluorescein diacetate and a fluorescence plate reader; the cytokinome was analysed using an array profiler, ELISA and RT-PCR. Receptors binding to JP2 were isolated using a novel immunoprecipitation assay and validated functionally using specific blocking antibodies. Results: JP2 and non-JP2 survival was comparable between all the neutrophil groups. Resistance to neutrophil necrosis following exposure to JP2 was significantly lower in the MIPP group, than in all the other groups (p<0.0001). Conversely, MIPP neutrophils showed lower levels of ROS production in response to JP2 infection compared with that of healthy neutrophils (p<0.001). Furthermore, significantly lower levels of cytokines, such as IL8, IL10 and TNFα, were observed during JP2 incubation with MIPP neutrophils than upon incubation with periodontally healthy neutrophils. Various proteins expressed on neutrophils bind to JP2. Of these, CD18 was found to mediate neutrophil necrosis. The CD18 receptor on MIPP neutrophils acts differently from that on periodontally healthy patients neutrophils, and appears to reflect differential neutrophil reactions to JP2. Conclusion: The study portrays a fundamental difference in neutrophil response to JP2 infection between periodontally healthy and MIPP patients. This was evident in the resistance to necrosis, and lower ROS and cytokine production, despite the persistent presence of viable JP2. Whilst in periodontally healthy neutrophils, JP2 binds to CD18 on cell surfaces, this is not the case in MIPP neutrophils, suggesting a potential role for CD18 in the periodontal susceptibility of MIPP patients.